Impact of Eradication on the Risk of Incident Nonalcoholic Fatty Liver Disease: A Cohort Study - Ji Won Kim; Tae Jun Kim; Ji Eun Kim; Ji Eun Na; Hyuk Lee; Byung-Hoon Min; Jun Haeng Lee; Poong-Lyul Rhee; Jae J Kim (Yong Chan Lee, 2022)
Background/Aims Previous studies have reported an association between Helicobacter pylori (H. pylori) infection and nonalcoholic fatty liver disease (NAFLD). Our study examined whether eradication for H. pylori infection reduces the risk of incident NAFLD. Materials and Methods This retrospective cohort study examined 3,780 adults who had no NAFLD at baseline but were infected with H. pylori. The study population was followed from January 1995 until January 2020. H. pylori infection was determined by an H. pylori-specific IgG antibody test. Fatty liver was diagnosed by ultrasound. Results During a median follow-up of 7.9 years, 1,294 participants developed NAFLD. In a multivariable model adjusted for age, sex, BMI, smoking status, alcohol intake, and metabolic variables, the uneradicated (for H. pylori) group exhibited a higher risk of incident NAFLD than the eradicated group (hazard ratio [HR], 1.36; 95% CI, 1.18~1.56). The multivariable analysis also demonstrated that higher BMI, current smoking and several metabolic abnormalities were significant risk factors for NAFLD. Subgroup analyses revealed that persistent H. pylori infection correlated with an increased risk of NAFLD. H. pylori eradication was associated with a decreased risk of NAFLD development. Conclusions H. pylori infection may have a pathophysiological role in NAFLD development. Hence, successful eradication of H. pylori decreases the risk of incident NAFLD.